A test of inter- and intra-observer error for an atlas method of combined histological data for the evaluation of enamel hypoplasia. (June 2015) - Primeau, Charlotte; Arge, Sara O.; Boyer, Charlotte; Lynnerup, Niels
Abstract: This report presents the dental chart data of Reid and Dean (2006) and Holt et al. (2012), combined into a single colour atlas for estimating age-at-defect formation of enamel hypoplasia. It is suggested that this dental chart may replace the dental chart of Massler et al. (1941), as data from Reid and Dean (2006) and Holt et al. (2012) takes into account hidden cuspal enamel and as such is considered more accurate. The colour atlas was tested for inter- and intra-observer error, using 177 teeth with linear enamel hypoplasia from 30 archaeological skeletons. Results indicate that the colour atlas presented here is an easy and consistent tool for estimating age of enamel hypoplasia formation on the incisors, canines, and first molars. The significant change of this approach is the use of histological data, known to be more accurate than previously published data, combined and presented in a single coloured dental atlas facilitating the evaluation of enamel hypoplasia in the field and laboratory.